Al-Qur'an, Kemandirian Ekonomi Umat, dan Pendidikan Kewirausahaan Berbasis Maqashid Syariah di Era Society 5.0 - Nurhuda, Abid; Pranoto, Ahmad Hadi; Huda, Ali Anhar Syi'bul; Putri, Yulita (SENTRI: Jurnal Riset Ilmiah, 2025)
The disparity between the size of Indonesia’s Muslim population and the low level of Islamic financial literacy—which stands at just 39.11 per cent—serves as the starting point for this study; a paradox that raises questions about the extent to which the economic values set out in the Qur’an have truly been incorporated into the educational practices of the Muslim community. Using a literature review method with a thematic exegesis (tafsir maudhu’i) approach, this study examines verses on work ethic and the ownership of wealth through four exegetical works (Ibn Kathir, Al-Qurṭubī, Al-Mishbah, and Al-Azhar), combined with a content analysis of literature on the maqāshid al-sharī’ah and contemporary entrepreneurship education. The findings reveal that the four exegetes, despite differing eras and geographical contexts, concur in viewing economic activity as a sphere of worship that is inseparable from social and national responsibilities, with hifz al-mal serving as a proactive framework that encourages endeavour, rather than merely a defensive prohibition. This research proposes a model for a Qur’anic entrepreneurship education ecosystem that integrates a maqashid-based curriculum, contextual pedagogy in the tradition of Nusantara exegesis, and the prudent utilisation of Society 5.0 technologies. These findings affirm that the economic self-reliance of the Muslim community is not an ideal existing outside the guidance of divine revelation, but rather a trust awaiting revival through concrete educational curricula and policies.